Case Report: Left ventricular pseudoaneurysm presenting with ventricular tachycardia - Esra Polat; Mahmut Arslan; Yusuf Çorbacıoğlu; Ahmet Khalousi; Rauf Önder; Candan Güngör (Frontiers in Cardiovascular Medicine, 2026)
Left ventricular pseudoaneurysm is a rare and life-threatening disorder that can present with a wide range of clinical manifestations, from an asymptomatic disease to sudden cardiac death. This case report presents a 38-year-old patient with no history of cardiovascular disease who presented with ventricular tachycardia and was diagnosed with left ventricular pseudoaneurysm following multiple cardiac imaging investigations. Given the high risk of rupture, early diagnosis of this rare condition is of critical importance, as early surgical intervention can be lifesaving.